THE IMPACT OF FAMILY CONTROL AND SIZE ON CAPITAL STRUCTURE DECISIONS - Ramalho, Joaquim (2014)
This paper examines the following three hypotheses about which there is some lack of clarification in the financial literature: i) family ownership is a relevant factor in determining firms’ financing decisions; ii) family ownership has a different influence on the use of debt from determining its proportion; and iii) the differentiated influence of the family ownership factor on the decision to use long-term debt and on its proportion depends on firm size. Using a binary choice model to explain the probability of the firm using debt and a fractional data model to explain the proportion of debt issued, we find strong support for the first and third hypotheses. Particularly, we find that: i) depending on size, family ownership influences positively the probability of using debt; ii) depending on size and the use of debt, family ownership influences positively the proportion of debt used.